2014
DOI: 10.1063/1.4856815
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and vibronic properties of a discotic liquid-crystal and its charge transfer complex

Abstract: Discotic liquid crystalline (DLC) charge transfer (CT) complexes combine visible light absorption and rapid charge transfer characteristics, being favorable properties for photovoltaic (PV) applications. We present a detailed study of the electronic and vibrational properties of the prototypic 1:1 mixture of discotic 2,3,6,7,10,11-hexakishexyloxytriphenylene (HAT6) and 2,4,7-trinitro-9-fluorenone (TNF). It is shown that intermolecular charge transfer occurs in the ground state of the complex: a charge delocali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The axial orientation could be desirable for organic electronic applications. 33 The results of this study can help guide the design of hybrid LCÀinorganic systems with desired column arrangements.…”
Section: Resultsmentioning
confidence: 96%
“…The axial orientation could be desirable for organic electronic applications. 33 The results of this study can help guide the design of hybrid LCÀinorganic systems with desired column arrangements.…”
Section: Resultsmentioning
confidence: 96%
“…1,2 Research on DLCs over the last few decades has shown that they can be considered promising materials for use in electronic applications as they exhibit one-dimensional high charge mobility along the axis of the column in the columnar mesophase. [3][4][5][6] The hexagonal columnar mesophase is commonly formed by DLCs, between plastic crystalline and isotropic phases as the molecules can self-organize and stack into columns, which is driven by the favorable p-p interaction between the aromatic cores. Hence, the self-assembly results in favorable charge transport along the axis of the column due to the delocalization of p-electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several attempts have been made regarding the synthesis of charge transfer (CT) complexes due to their structural applications in different branches of chemistry including organic semiconductors [ 1 , 2 ], photocatalysts [ 3 ], biological complexes [ 4 , 5 , 6 ], liquid crystals [ 7 ] and many more. Owing to their importance, since they can also act as an intermediate molecule or can have transitory existence in some important chemical reactions, efforts have been made by scientists to understand their synthetic applications.…”
Section: Introductionmentioning
confidence: 99%
“…liquid crystals [7] and many more. Owing to their importance, since they can also act as an intermediate molecule or can have transitory existence in some important chemical reactions, efforts have been made by scientists to understand their synthetic applications.…”
Section: Introductionmentioning
confidence: 99%